Sequence analysis of tumor necrosis factor-α (TNF-α) promoter, 5'UTR and exon1 and association of rs361525 (-238 G>A) with BMI - al-Rashid, Maryam H.; Husayn, Rubina F.; al-Bustan, Suzanne A.; Barhush, Sahar A. (Kuwait journal of science, 2023)
Obesity is among the most common complex diseases with a high rate of morbidity and mortality globally and locally in Kuwait. Tumor Necrosis Factor-alpha (TNF-α) is a pro-inflammatory cytokine that is primarily secreted by monocytes/macrophage. Increased expression of TNF-α level had been observed in the adipodse tissue of obese cases that could disrupt lipid metabolism and lead to the development of obesity and obesity-related diseases. The human TNF-α promoter exhibits a high number of genetic variants, mainly single nucleotide polymorphisms (SNPs) that had never been fully reported in Arabs. Sequencing of the TNF-α promoter, 5' UTR, and exon 1 in 290 Kuwaiti Arabs has identified 14 genetic variants, including one novel SNP. Two promoter SNPs; rs1800750 (-376G>A) and rs361525 (-238G>A) has been found in strong linkage disequilibrium (r2 = 0.73) and (D′ = 1, LOD = 32). Linear and logistic regression analysis in 863 samples of Kuwaiti general population, have not shown any significant association in carriers of the A allele of rs361525 with continuous and categorical BMI, respectively. This is the first study in the Middle east and Kuwait that has sequenced and identified the common, rare and novel genetic variants of TNF-α promoter, 5'UTR and exon 1 in Arabs.